A biodegradable magnesium alloy vascular stent structure: Design, optimisation and evaluation. (1st April 2022) - Li, Yafei; Wang, Yan; Shen, Zhenquan; Miao, Fulong; Wang, Jianfeng; Sun, Yufeng; Zhu, Shijie; Zheng, Yufeng; Guan, Shaokang
Abstract: The existing biodegradable magnesium alloy stent (BMgS) structure is prone to problems, such as insufficient support capacity and early fracture at areas of concentrated stress. Herein, a stent structural design, which reduced the cross section of the traditional sin-wave stent by nearly 30% and introduces a regular arc structure in the middle of the support ring. The influence of the dual-parameter design of bending radius ( r ) and ring length ( L ) on plastic deformation, expansion and compression resistance performances are discussed. The non-dominated sorting genetic algorithm II (NSGA-II) was used to search for the optimal solution. It was found that the introduction of parameter r effectively improved the plastic deformation and expansion performance, and the reduction of L improved stent compression resistance. Finally, an optimized stent configuration was obtained. In vitro mechanical tests, including balloon inflation, radial strength and flexibility, verified the simulation results. The radial strength for the optimised stent increases by approximately 40% compared with that for the sinusoidal stent. Microarea X-ray diffraction result shows that the circumferential residual stress for the optimised stent decreases by half compared with that for the sinusoidal stent, thus effectively reducing the stress concentration phenomenon. Statement of significance : Despite current progress in BMgS research, the optimal design of the structure is limited. We present a new type of structurally designed stent. The performance of this stent was analysed by a finite element method and experimentally verified. The structural design positively influenced stent performance. Graphical abstract: Image, graphical abstract